LEMBAGA PERMASYARAKATAN KELAS IIA DENGAN PENEKANAN PANOPTICON ARCHITECTURE DI GORONTALO - S. Puluhulawa, Faisal; Mannan, Abd; Tamrin, Moh. Muhrim (Program Studi Teknik Arsitektur, Fakultas Teknik - Universitas Ichsan Gorontalo, 2023)
This research aims to: 1) find the right place and site for the Class IIA Correctional Institution in Gorontalo close to other supporting facilities so that prisoners can reach it easily, 2) create a building form that has characteristics, including building functions, 3) determine the pattern of space relations so that it can be controlled from all directions. This research is design research in realizing the design of the Class IIA Correctional Institution in Gorontalo. The data in this research are obtained by direct observation, documentation method, literature study, internet study, and the comparative method. Based on the data obtained, this research results in the design of the desired penitentiary design. The stage carried out after data collection is the strengthening of the design concept based on the concept of the approach applied. Lastly, this research produces the design drawings of the Correctional Institution